DAMPAK BISNIS PARIWISATA TERHADAP MASYARAKAT LOKAL: STUDI DAMPAK BISNIS PARIWISATA TERHADAP HAK ASASI MANUSIA - Kurniawan, Arief Rianto; Primawardani, Yuliana (Jurnal Legislasi Indonesia, 2021)
Referring to tourism regulations, tourism development aims to increase economic growth, improve community welfare, poverty, and overcome unemployment. The study results explain that the involvement of corporations in the tourism business in tourism development in Labuan Bajo, Komodo, Indonesia has an impact on human rights. Five types of tourism businesses that have an impact on human rights, namely: tourist attractions and tourist areas, entertainment and beverage businesses, accommodation and food businesses, tourism transport businesses, and recreational and entrepreneurial businesses. The relationship between the impact of the tourism business and human rights is formed when on the one hand the interest of tourism development is to improve the economy at the local and national levels, but on the other hand, the involvement of private and foreign corporations tends to override the rights of local communities. This research is an analytical descriptive study, which refers to the research results and literature related to the discussion. This study concludes that there is a gap in the acceptance of economic benefit values for local communities from tourism development because there is discrimination in government policies against the opportunity and convenience of conducting tourism businesses, which are more likely to be given to corporations.